Misconception Analisis of Junior High School Student in Lareh Sago Halaban Distrit on Vibration, Wave and Sound Materials Using the Four Tier Test Instrument - Ulfah Mardyah; Khairil Arif; Azza Nuzullah Putri; Yurnetti Yurnetti; Deasy Silvia; Yohana Permata Sari (Postgraduate, University of Mataram, 2024)
The purpose to analyse the student’s misconception profile and determine the percentage of misconceptions of class VIII students on vibration, wave, and sound material. The reseacrh subjects 78 students in two acceredited A secondary schools during the full 2023-2024 semester. The research method is descritive quantitative. Data collection method using a diagnostic test with a four tier test of 21 questions developed by Merry Christiani and Vindy Utami Karomah was the modified by researchers with reliability of 0,86 (very high). The four tier test instrument consists of four levels. At the first level, there are multiple choice questions with four answer choices. The second level includes students' confidence in answering the first level questions. The third level is related to the reasons behind the answers students choose at the first level. Finally, the fourth level includes students' beliefs regarding the reasons for the answers at the third level. The results of the research show that the profile of students' misconceptions is on the indicators of the concept of vibration, the concept of amplitude and deviation, the concept of period, the concept of vibration frequency, the relationship between frequency and period, the basic concept of waves, the concept of sound and frequency, the sound propagation medium and the relationship between periods, frequency and wavelength. speed, is in the medium category while the creepage concept indicator is high. The conclusion of the research results is that the misconception of junior high school students in Lareh Sago Halaban District regarding vibration, wave and sound material using the Four Tier Test instrument is 55% in the medium category